The Effect of Mixed Hydrocolloids and Protein Isolate Film on the Physical-Mechanical Properties of Film and the Survivability of Lacticaseibacillus paracasei and Bifidobacterium animalis - Ploypetchara, Thongkorn; Srimongkoluk, Ubolwanna; Borompichaichartkul, Chaleeda; Ponyiam, Sasiwimon; Ruengsomwong, Supatjaree; Lekhavat, Supaporn (Science Essence Journal, 2023)
The effect of mixed hydrocolloids and protein isolate film on its physical-mechanical properties and the survival rate of Lacticaseibacillus paracasei and Bifidobacterium animalis that were added into the films were studied. The results showed the shear thinning behavior of the film solution. The agar mixed solution exhibited the highest apparent viscosity. The thickness and transparency of the film were varied from 0.0547±0.005 to 0.102±0.007 mm and 9.03±0.93 to 32.65±4.55, respectively. The films that consisted of soy protein isolate (SPI) had the highest thickness and the lowest transparency. The high mechanical properties were observed in the agar-incorporated film. Using glycerol as a plasticizer had higher elongation at break than using sorbitol. The survivability of each probiotic bacteria was found ranging from 41.84±0.46% to 92.58±2.20%, and the highest survivability was found in the film-incorporated protein isolate, while it was not found any probiotic bacteria in the agar film without protein. However, B. animalis had a greater survival rate in mixed film than L. paracasei. In summary, the application of probiotic film would depend on the component of mixed films and probiotic strains that affected physical-mechanical properties of the film and probiotic survivability.